2010
DOI: 10.1002/bmc.1390
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of atenolol and amiloride in pharmaceutical preparations by capillary zone electrophoresis with capacitively coupled contactless conductivity detection

Abstract: Capillary zone electrophoresis coupled with a capacitively coupled contactless conductivity detector (CE-C(4)D) has been employed for the determination of atenolol and amiloride in pharmaceutical formulations. Acetic acid (150 mm) was used as background electrolyte. The influence of several factors (detector excitation voltage and frequency, buffer concentration, applied voltage, capillary temperature and injection time) was studied. Non-UV-absorbing L-valine was used as internal standard; the analytes were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The atenolol (CAS number: 29122-68-7) with a purity of >98% was purchased from Tokyo Chemical Industry Co., Ltd. (Figure 1). It has a formula mass of 266.336 g/mol and a p value of 9.6 [1,[19][20][21]. Its solubility in pure water was 9.34 g/L [22].…”
Section: Methodsmentioning
confidence: 99%
“…The atenolol (CAS number: 29122-68-7) with a purity of >98% was purchased from Tokyo Chemical Industry Co., Ltd. (Figure 1). It has a formula mass of 266.336 g/mol and a p value of 9.6 [1,[19][20][21]. Its solubility in pure water was 9.34 g/L [22].…”
Section: Methodsmentioning
confidence: 99%
“…A CE‐C 4 D method for determination of trifluoroacetic acid was developed and validated (Al Azzam et al ., ). The analyses were performed under optimized conditions using BGE composed of 20 m m MES and 20 m m l ‐His pH 6.1 was used.…”
Section: Pharmaceutical Analysismentioning
confidence: 97%
“…Al Azzam et al () have demonstrated the simultaneous determination of atenolol (AT) and amiloride (AM) in pharmaceutical formulations using CE with contactless conductivity detector. Acetic acid (150 m m ) was used as BGE.…”
Section: Pharmaceutical Analysismentioning
confidence: 99%